Evidence on climate and soil co-benefits of improved forage grasses in Tanzania generated through integrated modelling - CGIAR Research Program on Livestock (2021)
The evidence from various sites in Tanzania has been published in peer-reviewed papers, made accessible through communication packages and has been initially shared with stakeholders who prioritized policy opportunities. Next users, including private and public decision makers, can now make use of this evidence, to inform their programmatic decisions.